2013
DOI: 10.3389/fpsyg.2013.00193
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Processing Altruism

Abstract: Altruism refers to an other-benefiting behavior that is costly but bears no direct profit to oneself. At least three different forms can be distinguished: help giving, altruistic punishment, and moral courage. We investigated the differential impact of two thinking modes, intuitive (System 1) and rational (System 2), on these three altruistic behaviors. Situational (state-related) thinking style was manipulated via experimental instructions and generally preferred thinking style (trait-related) was assessed vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 45 publications
1
38
2
Order By: Relevance
“…Only 18 % of the participants chose to donate. Previous studies with a non-obvious option to give to a charity have found a high percentage (30-45 %) but a low value (less than a dollar or an euro) of the donations (Blaszczynski, Gainsbury, & Karlov, 2014;Kinnunen & Windmann, 2013). The relatively low percentage in the current study is surprising since the value of the Amazon voucher was determined by a pilotstudy and there was no reputation bias of the charity as the participants were free to choose any charity they desired to donate to.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Only 18 % of the participants chose to donate. Previous studies with a non-obvious option to give to a charity have found a high percentage (30-45 %) but a low value (less than a dollar or an euro) of the donations (Blaszczynski, Gainsbury, & Karlov, 2014;Kinnunen & Windmann, 2013). The relatively low percentage in the current study is surprising since the value of the Amazon voucher was determined by a pilotstudy and there was no reputation bias of the charity as the participants were free to choose any charity they desired to donate to.…”
Section: Discussioncontrasting
confidence: 50%
“…While large body of research has focused on negative interactions and cyberbullying on the Internet (see, e.g., Calvete, Orue, Estévez, Villardón, & Padilla, 2010), very little is known about prosocial behavior online, particularly when this behavior is not limited to social-media interactions with friends and family (Correa, Hinsley, & De Zúñiga, 2010) or gaming societies (e.g., Ang & Zaphiris, 2010;Wang & Wang, 2008). While prosocial behavior can encompass a large variety of otherregarding actions, in this study we focus on help-giving and moral courage: Two other-benefiting behaviors that are costly to the actor and have been in previous research suggested to be facets of a more general altruism construct (Kinnunen, Singh, & Windmann, 2015;Kinnunen & Windmann, 2013). We will examine how individual Moral courage manifests as a willingness to take action in situations that conflict with person's moral or sense of what is just (see, e.g., Lodge & Frydenberg, 2005;Poteat & Vecho, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Zhong (2011) found that participants give more to a charity organization (Child Family Health International) when they are asked how much they feel to give compared to when they are asked how much they decide to give. Finally, Kinnunen and Windmann (2013) found no differences in donations to Greenpeace.…”
Section: Review Of the Empirical Evidencementioning
confidence: 82%
“…Cognitive primes studies Small et al (2007) Charitable giving Intuition increases giving, but only when the target is identifiable and not when is statistical Zhong (2011) Charitable giving "Feel" increases giving, compared to "Decide" Kinnunen & Windmann (2013) Charitable giving Intuition has no effect on giving, compared to Deliberation Ego depletion studies Halali et al (2013) Dictator game Depletion decreases frequency of equal split Achtziger et al (2015) Dictator game Depletion decreases giving Ferrara et al (2015) Dictator game Sleep restriction decreases giving, but only among females Banker et al (2017) Dictator game Depletion has no effect on giving, it only makes participants more likely to choose the status quo Dickinson & McElroy (2017) Dictator game Sleep restriction decreases giving Rantapuska et al (2017) Charitable giving Hunger has no effect on giving Itzchakov et al (2018) Charitable giving Depletion decreases giving, but only when giving is accompanied by a persuasion message Neurostimulation studies Ruff et al (2013) Dictator game rLPFC stimulation decreases giving, relative to sham; rLPFC inhibition increases giving Strang et al (2015) Dictator game DLPFC stimulation increases giving, relative to sham; DLPFC inhibition decreases giving Gross et al (2018) Dictator game rLPFC inhibition has no effect on altruism or selfishness, but only makes people more likely to follow rules of behavior…”
Section: Charitable Givingmentioning
confidence: 99%